Perlindungan Hukum terhadap Nasabah Atas Kerusakan atau Kehilangan Barang Jaminan (Studi pada PT. Pegadaian PERSERO Unit Aur Kuning Bukittinggi) - Viola Audra Jhunia; Mahlil Adriaman (LPPM Institut Pendidikan Nusantara Global, 2026)
This research discusses the legal protection of customers for damage or loss of collateral at PT. Pawnshops (Persero), especially PT. Pawnshop Aur Kuning Unit Bukittinggi Branch. Pegadaian is one of the non-bank financial institutions that provides credit facilities with a pawn system for the public by providing collateral in the form of a pawn agreement. Goods that can be used as collateral in a pawn agreement are gold jewelry, motor vehicles, electronic goods, and property certificates that have economic value for the owner. In practice, the collateral will be stored by the pawnshop safely during the agreement period, but it is also possible if there will be damage or loss of the customer's collateral due to negligence or force majeure. The oni research aims to analyze the form of legal protection provided to customers in the event of loss or damage to collateral by using the Empirical Juridical research method, namely researching and interviewing directly with PT. Pegadaian (Persero) Aur Kuning Unit.